THE IMPORTANCE OF CIRCULATING TUMOR DNA IN THE ASSESSMENT OF METASTATIC COLORECTAL CANCER TREATMENT EFFECTIVNE - M. I. Sluzhev; V. V. Semiglazov; T. Yu. Semiglazova; E. V. Tkachenko; S. A. Protsenko; D. Kh. Latipova; S. V. Kondratev; N. A. Brish; Yu. V. Alekseeva; A. M. Belyaev (Сибирский онкологический журнал, 2021)
Challenges in cancer detection, prognosis and management are currently being solved by determining circulating tumor DNA (ctDNA). The assessment of this marker has acquired particular importance in metastatic colorectal cancer (mCRC), the systemic treatment of which depends on the RAS gene status, which has prognostic and predictive value. However, the possibilities of taking samples from the primary or metastatic lesion for pathomorphological and molecular analysis in CRC are often limited. The determination of ctDNA using liquid biopsy has an advantage over standard biopsy due to its low invasiveness and high availability of the method. Analysis of mutations using ctDNA as well as changes in the level of this marker is a criterion for the effectiveness of systemic treatment, as well as a factor that determines the risk of disease progression. Currently, the potential of using ctDNA to monitor effectiveness of first-and second-line chemotherapy, as well as to predict the development of secondary resistance to EGFR inhibitors (cetuximab and panitumumab) in the first-line treatment and assessment of RAS status for returning to therapy with EGFR inhibitors in the third-line treatment of mCRC is being studied. Several pilot studies have provided evidence of the efficacy of EGFR re-treatment. The modern literature data published in leading peer-reviewed journals in Russian and international scientific citation databases, such as Medline, Elibrary, and PubMed were analyzed. Of the 138 analyzed publications, 56 were used to write this review.